Global prevalence and molecular characteristics of three clades within hepatitis B virus subgenotype C2: Predominance of the C2(3) clade in South Korea - Kim, Dong Hyun; Choi, Yu-Min; Jang, Junghwa; Kim, Bum-Joon (Frontiers in Microbiology, 2023)
Hepatitis B Virus (HBV) genotypes reflect geographic, ethical or clinical traits and are currently divided into ten genotypes (A-J). Of these, genotype C is mainly distributed in Asia, is the largest group and comprises more than seven subgenotypes (C1–C7). Subgenotype C2 is divided into three phylogenetically distinct clades, C2(1), C2(2) and C2(3), and is responsible for most genotype C infections in three East Asian nations, including China, Japan, and South Korea, which are major HBV endemic areas. However, despite the significance of subgenotype C2 with regard to clinical or epidemiologic aspects, its global distribution and molecular characteristics remain largely unknown. Here, we analyze the global prevalence and molecular characteristics between 3 clades within subgenotype C2 using 1315 full genome sequences of HBV genotype C retrieved from public databases. Our data show that almost all HBV strains from South Korean patients infected with genotype C belong to clade C2(3) within subgenotype C2 [96.3%] but that HBV strains from Chinese or Japanese patients belong to diverse subgenotypes or clades within genotype C, suggesting clonal expansion of a specific HBV type, C2(3), among the Korean population. Our genome sequence analysis indicated a total of 21 signature sequences specific to the respective clades C2(1), C2(2) and C2(3). Of note, two types of four nonsynonymous C2(3) signature sequences, sV184A in HBsAg and xT36P in the X region, were detected in 78.9% and 82.9% of HBV C2(3) strains, respectively. In particular, HBV strains C2(3) versus C2(1) and C2(2) show a higher frequency of reverse transcriptase mutations related to nucleot(s)ide analog (NA) resistance, including rtM204I and rtL180M, suggesting an increased possibility of C2(3) infection in those with NA treatment failure. In conclusion, our data show that HBV subgenotype C2(3) is extremely prevalent in Korean patients with chronic HBV infection, which is distinct from two other East Asian nations, China and Japan, where diverse subgenotypes or clades within genotype C coexist. This epidemiologic trait might affect distinct virological and clinical traits in chronic HBV patients in Korea, where exclusively C2(3) infection is predominant.